Diabetes mellitus and its association with oral squamous cell carcinoma: a review of the literature (Research, Society and Development, 2022)
Oral squamous cell carcinoma is a malignant tumor characterized by the uncontrollable, excessive, and irreversible proliferation of squamous cells of the oral epithelium, representing most of all oral cancers. Interestingly, despite advances on therapeutic procedures such as radiotherapy, chemotherapy, and surgical techniques, the survival rate has not improved in recent decades. On the other hand, diabetes mellitus is a chronic disease with clinical presentations and metabolic disorders characterized by increased blood glucose levels. Various studies suggest a possible relationship between these two entities; evidencing that a person with diabetes and, in addition, poorly controlled, may have many oral manifestations, such as the possible development of oral malignant lesions. This manuscript aims to present and discuss the updated scientific evidence on the relationship between diabetes mellitus and oral squamous cell carcinoma.